Religion and Equality in the Reservations to the Convention on the Elimination of All Forms of Discrimination Against Women - Mut, María (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2023)
Despite the significant absence of the United States of America, the vast majority of States of the international community are parties to the Convention on the Elimination of All Forms of Discrimination against Women. However, regarding other conventions, this is the Convention which has the largest number of reservations aimed to modify or exclude most of its provisions. After examining the reservations, this paper argues that a large part of them have to do with the difficult relationship concerning, on the one hand, the right of equality between men and women, enshrined in the Convention, and, on the other, the right of religious freedom, which it is not expressly reflected in the Convention. The Convention is silent on how both human rights are related and does not articulate any type of measure aimed to balancing and making them compatible. This affects both directly and indirectly the interpretation of the Convention and the work of the Committee on the Elimination of All Forms of Discrimination against Women.